2011
DOI: 10.1007/s11434-010-4322-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an anti-diethylstilbestrol monoclonal antibody and development of an indirect competitive ELISA to detect diethylstilbestrol in biological samples

Abstract: Based on the preparation of an anti-diethylstilbestrol (DES) monoclonal antibody, a simple and convenient indirect competitive enzyme-linked immunosorbent assay (ELISA) method for DES detection has been developed. The monoclonal antibody demonstrated high sensitivity to DES with an IC 50 value of 275 pg mL -1 and detection limit (LOD) of 90 pg mL -1 . The specificity of the assay was studied by measuring cross-reactivity of the antibody with structurally related compounds of ethinyl estradiol (<7%), estrone (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Table 2 shows the CR of anti-HES mAb with different compounds. It was obviously noticed that there was no significant CR with other estrogen used in this study; this finding was in agreement with other research reported on stilbene antibodies (Li et al, 2011;Wang et al, 2008). Therefore, the results revealed that the produced 2E6 mAb had a high specificity against HES and more affinity against DES.…”
Section: Sensitivity and Specificity Of Anti-hes Monoclonal Antibody supporting
confidence: 92%
See 1 more Smart Citation
“…Table 2 shows the CR of anti-HES mAb with different compounds. It was obviously noticed that there was no significant CR with other estrogen used in this study; this finding was in agreement with other research reported on stilbene antibodies (Li et al, 2011;Wang et al, 2008). Therefore, the results revealed that the produced 2E6 mAb had a high specificity against HES and more affinity against DES.…”
Section: Sensitivity and Specificity Of Anti-hes Monoclonal Antibody supporting
confidence: 92%
“…The synthesis of 4-(4-(4-(4-hydroxyphenyl)hexan-3-yl)phenoxy)butanoic acid (HES-4C) was accomplished by linking ethyl 4 bromobutanoate to one of HES ′ -OH group using the method as described by Li et al (2011) and Wang et al (2008) with slight modification (Figure 1). Briefly, 200 µl of ethyl 4 bromobutanoate dissolved into 1 ml of DMSO was slowly introduced into a solution of 15 ml of DMSO containing 0.5 mg of HES and 0.25 g of K 2 CO 3 ; then, the mixture was heated to 60°C for 6 h. After cooling to room temperature, the mixture was extracted with Diethyl ether and the ether extract was dried in fume hood; the product obtained was saponified to produce HES-4C acid.…”
Section: Hapten Synthesis and Immunogen Preparationmentioning
confidence: 99%
“…20) In addition, icELISA methods were developed for detection of okadaic acid and dinophytoxin-1 in seafood, 21) and diethylstilbestrol in biological samples. 22) Pharmacokinetic studies are very important in drug development. Currently, high-performance liquid chromatography (HPLC), 23) HPLC-mass spectrum (MS)/MS, 24) gas chromatography (GC) 25) and GC-MS 26) are the main methods employed in pharmacokinetics.…”
Section: Pharmacokinetics Of Geniposide By Monoclonal Antibody-based mentioning
confidence: 99%
“…The limit of detection was determined as the concentration that caused 10% inhibition 14,20,21 and the linear range was determined as the concentrations that caused 20-80% inhibition in both ic-ELISA and CL-ELISA. Cross-reactivity was determined using the optimized CL-ELISA system and ic-ELISA and was calculated as follows: percentage of cross-reactivity ¼ 100 Â IC 50 (Cy4)/IC 50 (the tested compound).…”
Section: Sensitivity Linear Range and Specicitymentioning
confidence: 99%